Nine Clap Operated Device Control System - Jadhav, Rushikesh N.; Kothwal, Abhishek B (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
The clap operated system is help to accomplish requests without moving from the position, it is possible to switches ON & OFF the devices. This circuit helps to, those are physically challenged and the patient in hospital which are not able to get up from the bed. Simply functioned by clapping or need to puff in front of microphone. For first clap first device is gets turn ON, if continue with second clap then second device will get switch ON. It is possible up to four devices and it depends on output of decade counter. This system develops by using timer IC, it can build to operate in monostable mode. It is applicable to TV, Fan, Light, Motor & other home appliances. How to cite this article: Jadhav RN, Kothwal AB, Khalkar GH. Nine Clap Operated Device Control System. J Adv Res Appl Arti Intel Neural Netw 2019; 2(2): 24-27.